Off-farm participation and technical efficiency among smallholder farmers in the Northern Region, Ghana - Danso-Abbeam, Gideon; Abban, Brightina A.A.; Donkoh, Samuel A. (Applied Studies in Agribusiness and Commerce, 2017)
The study aimed at investigating the effects of off-farm participation on technical efficiency of maize production in the Tolon district of the Northern Region, Ghana. The Logit regression model was used to analyze the determinants of off-farm participation while the stochastic frontier production function was used to model the determinants of maize output and technical efficiency. The empirical results from the logistic regression model indicate that age of farmer, educational attainment, farming experience, farm size, and previous farm income are significant drivers of farmers’ participation in off-farm activities. Farmers’ average technical efficiency level was 90.7% suggesting a 9.3% potential loss to inefficiency. Moreover, participation in off-farm activities had a negative influence on farmers’ technical efficiency level. The study, therefore, recommends that farm-level policy should be directed towards making the agricultural sector attractive by promoting investment and agricultural employment opportunities in the rural areas so as to ensure full commitment to farming activities. JEL code: Q22